The Effectiveness of Talk Shows on Local Radio Stations in Sebha in Promoting Sustainable Environmental Awareness (A Field Study) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the topics covered by talk shows on local radio stations regarding environmental issues in the city of Sebha. It sought to determine the level of public interest in listening to talk shows that discuss environmental issues, as well as to evaluate the contribution of these talk shows to promoting sustainable environmental awareness. This research falls under descriptive studies and utilized a questionnaire as its primary tool. The study was applied to a sample of 75 individuals from the local community in Sebha.The study reached several key findings, most notably:-        The results showed: that the listening rate of the sample members to local radio stations in Sebha was mostly "sometimes" at a rate of 45.3%, while those who followed them "rarely" stood at 29.3%, and those who followed them "daily" accounted for 25.3%.-        The results indicated: that public interest in listening to environmental talk shows in Sebha was high, reflecting a strong engagement within the local community toward targeted environmental media.-        The findings concluded: that talk shows play a major role in raising awareness about the importance of preserving natural resources for the benefit of future generations.-        The findings concluded: that there is broad public consensus on the need to develop the performance of local media to better serve environmental issues and sustainable development in the city of Sebha.
Keywords: Talk Shows, Local Radio Stations, Sustainable Environmental Awareness, Sebha City